PENGARUH GAYA HIDUP , CITRA MEREK DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN HIJAB ZOYA (Studi Empiris Pada Konsumen Hijab Zoya di Kota Semarang) - Lia Novitasari, 15.05.51.0241; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2019)
The purpose of this research was to examine and analyze the influence of lifestyle, brand image, and celebrity endorser on Zoya hijab purchasing decisions. The research uses survey methods with questionnaires as a data collection tool. The population of this study is all people in the city of Semarang. The research sampling technique was purposive sampling with the criteria of consumers who had bought and used Zoya's hijab. Data analysis using multiple linear regression. The results showed that lifestyle has a positive and significant effect on purchasing decisions. Furthermore, brand image has a negative and not significant effect on purchasing decisions and celebrity endorser has a positive and significant effect on purchasing decisions.